2013
DOI: 10.1093/aje/kws333
|View full text |Cite
|
Sign up to set email alerts
|

Iodine Supplementation During Pregnancy and Infant Neuropsychological Development: INMA Mother and Child Cohort Study

Abstract: Iodine supplementation during pregnancy is a common practice in developed countries. However, scant evidence is available regarding the safety and effectiveness of maternal iodine supplementation with regard to child neuropsychological development. We previously reported an inverse association between iodine supplementation and the psychomotor development of infants in a birth cohort from Valencia, Spain. In the present study, we assessed this association in a wider sample of mother and child pairs from 3 othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 30 publications
1
64
0
5
Order By: Relevance
“…In this study we examined the associations in women with iodine intake from food below and above the EAR (160 mg/d) separately because the effect of supplemental iodine might depend on previous iodine status. Our findings of no beneficial effects and some indications of negative effects are supported by findings from the Environment and Childhood cohort in Spain in which an increased risk of low psychomotor (10,11) and mental scores (11) in children of women who reported intake of iodine from supplements $150 mg/d compared with <100 mg/d was observed. On the other hand, Velasco et al (49) reported a positive impact on psychomotor scores in children of mothers who received 300 mg I from supplements from the first trimester compared with controls in a nonrandomized intervention study.…”
Section: Figuresupporting
confidence: 85%
See 1 more Smart Citation
“…In this study we examined the associations in women with iodine intake from food below and above the EAR (160 mg/d) separately because the effect of supplemental iodine might depend on previous iodine status. Our findings of no beneficial effects and some indications of negative effects are supported by findings from the Environment and Childhood cohort in Spain in which an increased risk of low psychomotor (10,11) and mental scores (11) in children of women who reported intake of iodine from supplements $150 mg/d compared with <100 mg/d was observed. On the other hand, Velasco et al (49) reported a positive impact on psychomotor scores in children of mothers who received 300 mg I from supplements from the first trimester compared with controls in a nonrandomized intervention study.…”
Section: Figuresupporting
confidence: 85%
“…There is, however, a lack of evidence to support the recommendation for iodine supplements during pregnancy in areas with mild-to-moderate ID, and some studies have even indicated that supplemental iodine is associated with adverse effects on child neurodevelopment (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Nine RCTs (24,25,26,27,28,29,30,31,32) and eight observational studies (33,34,35,36,37,38,39,40) were included in the review. Seven RCTs were reported on the effects of maternal supplementation on maternal thyroid function (26,27,28,29,30,31,32,33,34,35,36,37,38,39,40). Of these, four RCTs also contained data on neonatal thyroid function (27,29,30,32).…”
Section: Study Selectionmentioning
confidence: 99%
“…In this latter study, as well as in others (36), the psychomotor development of these children was improved thus supporting iodine supplementation. Finally, a recent observational study has reported an association of low FT 4 with worse neurocognitive tests in daughters of mothers receiving potassium iodide supplementation during pregnancy (113,114). Taking all these data together, the more prudent position right now is not to treat isolated hypothyroxinemia due to the lack of evidence (115) of its effect and the inconsistency of FT 4 measurements, but to ensure sufficient iodine supply during and, even better, before pregnancy.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%